The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acssuschemeng.8b02534
|View full text |Cite
|
Sign up to set email alerts
|

Green Approach to Conductive PEDOT:PSS Decorating Magnetic-Graphene to Recover Conductivity for Highly Efficient Absorption

Abstract: Graphene hybrid material is a hot topic in the fields of electromagnetic interference (EMI) shielding and microwave absorption (MA). However, hybridization reduces the conductivity of graphene resulting in the dramatical decline of MA performance. Herein, a novel two-dimensional (2D) hybrid material of PEDOT:PSS-Fe3O4-rGO (P-GF) was fabricated by a green approach of decorating conductive PEDOT:PSS using molecular-atomic deposition routes. The electromagnetic properties and MA performance of the hybrid material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(52 citation statements)
references
References 52 publications
(78 reference statements)
1
51
0
Order By: Relevance
“…Moreover, as shown in Fig. 7d, EM waves can travel long distances with multi-reflected propagation paths inside the hybrids, resulting from the special layered structures of the WS 2 nanosheets [72]. Table 1 compares the EM wave absorption characteristics of some hybrid materials containing 2D materials reported in previous work [16,17,37,39,40].…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, as shown in Fig. 7d, EM waves can travel long distances with multi-reflected propagation paths inside the hybrids, resulting from the special layered structures of the WS 2 nanosheets [72]. Table 1 compares the EM wave absorption characteristics of some hybrid materials containing 2D materials reported in previous work [16,17,37,39,40].…”
Section: Resultsmentioning
confidence: 88%
“…As indicated, anchoring the nanoparticles onto FCMTs amplifies the conductive loss mechanism, compared to the FCMT/PAN composite. The observed notches at permeability curves are generated from the natural and exchange resonances 82 , 103 . It is found that CuCo 2 S 4 nanoparticles and FCMT/CuCo 2 S 4 nanocomposite showed the considerable imaginary part of permeability, derived from the intrinsic features of nanoparticles.…”
Section: Resultsmentioning
confidence: 95%
“…It can be seen that FCMTs, ornamented by CuCo 2 S 4 nanoparticles, indicated the augmented relaxation loss mechanism due to the intrinsic characteristics of FCMTs, nanoparticles, and PAN, as well as, the emerged exclusive interactions at heterogeneous interfaces. Conductive loss is the key factor, boosting the imaginary part of permittivity 53 , 103 . As indicated, anchoring the nanoparticles onto FCMTs amplifies the conductive loss mechanism, compared to the FCMT/PAN composite.…”
Section: Resultsmentioning
confidence: 99%
“…• Nanoparticles formation is slow Hydrothermal method [41,[48][49][50][51][52][53][54][55][56] It involves substance crystallization at high temperature and pressure.…”
Section: Discussion Of Articlesmentioning
confidence: 99%